2019
DOI: 10.1038/s41598-019-46710-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of the Ultrafast, Tunable and Broadband Optical Kerr Nonlinearity in Graphene

Abstract: Graphene’s giant nonlinear optical response along with its integrability has made it a vaunted material for on-chip photonics. Despite a multitude of studies confirming its strong nonlinearity, there is a lack of reports examining the fundamental processes that govern the response. Addressing this gap in knowledge we analyse the role of experimental parameters by systematically measuring the near-infrared spectral dependence, the sub-picosecond temporal evolution and pulse-width dependence of the effective Ker… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…Equation () also recovers the scaling of n 2, gr with pulse duration in the sub‐ps excitation regime as experimentally observed in refs. [8, 9]. Furthermore, as discussed in the Supporting Information, according to our theory, the nonlinear response is mainly introduced by the dynamical behavior of the temperature rather than chemical potential and its switching in sign is mainly produced by changes in the interband contribution.…”
Section: Comparison With Experiments In Literaturementioning
confidence: 73%
See 3 more Smart Citations
“…Equation () also recovers the scaling of n 2, gr with pulse duration in the sub‐ps excitation regime as experimentally observed in refs. [8, 9]. Furthermore, as discussed in the Supporting Information, according to our theory, the nonlinear response is mainly introduced by the dynamical behavior of the temperature rather than chemical potential and its switching in sign is mainly produced by changes in the interband contribution.…”
Section: Comparison With Experiments In Literaturementioning
confidence: 73%
“…The research results reported since then seem to point in different directions, and have made it a major challenge to fully understand graphene's nonlinear‐optical behavior. The experimental data include both positive‐ [ 4,9 ] and negative‐valued [ 6–8,12 ] effective nonlinearities with a magnitude compatible with that of Hendry's experiments, [ 3 ] as well as much smaller nonlinearities. [ 10 ] From the theory point of view, calculations for the perturbative nonlinearity χgrfalse(3false) [ 1,2 ] give rise to nonlinearities that are two orders of magnitude smaller than false|χnormalgr(3)false|0.33em107esu measured in the aforementioned experiments.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…We should also mention systems based on commercial fs lasers [ 22 , 33 , 34 , 35 ] allowing one to achieve time resolution of ≈100 fs, but with limitations due to the spectral broadening (i.e., spectral resolution is too low for Raman detection) and experimental setups designed for ultrafast, or more generally, pump-probe, spectroscopy [ 36 , 37 ]. The latter represent valuable possibilities to be considered, but they involve high costs and complex optical setups.…”
Section: Optical Kerr Gatementioning
confidence: 99%